Características acústicas do idioma alemão na interpretação de cantoras líricas brasileiras - Silva, Verônica Oliveira da (2014)
Introduction: in order to adequately prepare a musical piece, classical singers go through several studies. Among the main ones are: the process of reading the piece that involves learning of melodies (heights), rhythms, dynamics, agogic aspects demanded by the score, literary translation of the work, technical vocal study, interpretation and the correct enunciation of the text. Purpose: to identify the acoustic characteristics of the singing emission of the German language in the interpretation of Brazilian female classic singers. Method: five female Brazilian classical singers and one female native German classical singer were selected and sound recorded. These singers executed parts of the song cycle Frauenliebe und Leben by composer Robert Schumann and a part of Ludwig van Beethoven s Ninth Symphony. The consonants [ç] and [ŋ], and vowels [y], [Y], [ø:], [oe] and [ə] were selected for analysis. Then, the acoustic measures of duration of the consonants and vowels and vowel formants (F1, F2) were analyzed using the PRAAT software. Results: regarding the duration measurements: the German singer forms a single group when analyzing the absolute and relative duration of vowels and consonants, since to correctly sing musical pieces in the German language one needs to have knowledge not only of musical but also of grammatical elements of the language, in order to avoid pronunciation errors in situations such as singing a long vowel on a short note or a short vowel on a long note. When related to the other analyzed singers, singer B5 was the one that was closest to the reference in vowel and consonant duration measurements, followed by B1 and B4. On the other hand, B2 and B3 were further from the reference in the duration measurements. When F1 and F2 measurements of the Brazilian singers were compared to the values of native singer A and to the vowels of spoken Brazilian Portuguese, as far as F1 it was observed that, for each analyzed vowel, in an attempt to approximate it to the correct German pronunciation, the tongue was either elevated or lowered, and for F2 the tongue was either anteriorized or posteriorized. Conclusion: The Brazilian classical singers, when singing in the German language, in regard to duration measurements, usually emit vowels and consonants without relating them to what is registered in the score, which, in some moments may harm even the meaning of words. In regard to F1 and F2 measurements, most of the Brazilian singers approximated the analyzed vowels to those present in Brazilian Portuguese. The study of the German Language, associated to classical singing, and living as a student and singing in Germany proved to be aspects that enable a better enunciation of the German language